Study of Interleukin 6 in Rheumatoid Arthritis and Anemic Patients in Sudan - Samar Mirghani Sidahmed Osman; Olla Mirghani Seidahmed Osman; Ibrahim Khidir Ibrahim (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Rheumatoid arthritis is considered one of the most common, and particularly attacks the joint causing significant individual and community burden and resulting from immunological abnormalities. It has been found that IL-6 plays a key role in the development of this disease. Overall anemia of chronic disease and iron deficiency anemia are frequent causes of anemia in RA patients. This study to analysis serum IL6 and to detect frequency of anemia/non-anemia and Rheumatoid arthritis (RA) patients and establish relationship between blood parameters and disease activity among Sudanese patients suffering from rheumatoid arthritis and deficiency anemia in Khartoum State.MethodsIt is a descriptive case-control study that involved 74 patients of both genders of RA, Anemia and non-anemic disease duration was two years. This study was conducted in Khartoum State. Complete Blood Count (CBC) was performed using the Auto Hematology Analyzer. Serum concentrations of IL-6, was measured in all patients and healthy individual using CLIA. The data collection was simple questionnaire and self-interview.ResultsThe frequency of the RA within anemic and non- anemic patients was found higher in females 46(62.16%) than in males 28(37.83%). The overall analysis showed significant changes in most of blood parameters between the age groups. A statistically significant association was found between the WBCs, RBCs and MCH blood parameters with IL6 among RA/anemia's patients with Chi square p-value = 0.001,0.013 and 0.014, respectively. The statistic odd ratio was found 5.828 and 5.703 for WBCs and RBCs. This increase was highly significant among RA-Anemia patients in particular. ConclusionOur study reported the blood parameters isolates which harbored the IL6 and their association with rheumatoid arthritis and Anaemia which possibly cause the disease symptoms. Anemia is an important complication in rheumatoid arthritis (RA) which is associated with physical disability and increased mortality. Among various mechanisms, recent studies suggest the central role of hepcidin and IL-6 for the pathophysiology of Anemia.
Keywords: Anemia; Hepcidin; Rheumatoid Arthritis; Interleukin-6; Blood Parameters